Prospects For the Development of The Activity of Business Subjects on The Base of The Sustainability Rating - Salimov Sherzod Bakhtiyorovich (Peerian Journals Publishing, 2024)
In this article, we will look at how the state uses taxes to manage and regulate business activity, as well as how the “sustainability rating of business entities” affects various aspects of the business environment. Understanding the mechanisms of business regulation through taxes will help to better understand the importance of tax policy in economic development and improving the business climate.
Keywords: entrepreneurship; sustainability rating; income tax